CASE REPORT: RADIOTERAPI PADA KARSINOMA PALATUM DURUM - R Suryoseto (Lembaga Pengembangan Kinerja Dosen, 2022)
An 64 –year-old male notice a tumor on the palate. Physical examination revealed a 6x5 cm exophytic tumor on the right side of the hard palate. The lesion extended posteriorly to involve the anterior part of the soft palate, laterally onto the right upper alveolar ridge, medially approaching the mid line, and anteriorly to the level of the first pre molar right . There was no palpable adenopathy in the neck. A CT scan confirmed the physical findings and also showed involvement of the floor of the maxillary sinus with bone destruction. A biopsy showed moderated to bad differentiated SCC. Stage T4aN0M0. OS reject underwent a left intra oral palatectomy and maxillectomy. OS agree to undergo kemotherapy, but after only 3 cycles OS was unable to continue therapy because the side effects were severe, OS felt his weight lost 15 kg because food could not enter, then OS was sent to the radiotherapy department to immediately undergo radiation. OS received radiotherapy with 3D conformal, EBRT with chemo for T4a doses are 2 Gy/ fx, to 66 Gy, field cover the primary with 2 cm margins. Dose limitations: Spinal cord maximum dose ≤ 45 Gy . Brain steam maximum dose ≤ 54 Gy, Keep 50% of the volume of each parotid ≤ 20 Gy (if possible) and mean dose < 26 Gy, Mandible maximum point dose ≤ 70Gy. The results of follow-up OS with physical examination and CT scan 2 months and 1 year 5 months after radiation concluded that the completed response and side effects can be tolerated well.